An in silico drug repurposing pipeline to identify drugs with the potential to inhibit SARS-CoV-2 replication - MacMahon, M.; Hwang, W.; Soorin Yim; MacMahon, E.; Abraham, A.; Barton, J.; Mukunthan, T.; Bilokon, P.; Vasanthi Priyadarshini, G.; Namshik Han (Elsevier, 2023)
Background: Drug repurposing provides an opportunity to redeploy drugs, which are already tested for safety or approved for use in humans, for the treatment of diseases distinct from their primary indication. For example, the repurposing of dexamethasone and baricitinib has played a crucial role in saving patient lives during the SARS- CoV-2 pandemic. There remains a need to expand therapeutic approaches to prevent life-threatening complications in vulnerable patients with COVID-19. Method: Using an in silico approach based on structural similarity to drugs already in clinical trials for COVID-19, potential drugs were predicted for repurposing. For a subset of identified drugs with different targets to their corresponding COVID-19 clinical trial drug, a mechanism of action analysis based on affected pathways in the context of the first 24 h of infection was applied to establish whether they might have a role in inhibiting the replication of SARS-CoV-2. Results: Twenty-nine structurally similar drugs with potential for repurposing against COVID-19 were predicted. Two of these with the potential to inhibit SARS-CoV-2 replication were identified using mechanism of action analysis. Triamcinolone is a corticosteroid that is structurally similar to dexamethasone; gallopamil is a calcium channel blocker that is structurally similar to verapamil. Conclusion: The identification of these drugs as potentially useful for patients with COVID-19 who are at a higher risk of developing severe disease supports the use of in silico approaches to facilitate quick and cost-effective identification of drugs for repurposing. Such drugs could expand the number of treatments available to the subset of patients who are not fully protected by vaccination.
Keywords: COVID-19; Triamcinolone; Gallopamil; Drug repurposing; Artificial neural network; Drug mechanism; Virus replication